The Ledgers of Merit and Demerit : Social Change and Moral Order in Late Imperial China - Brokaw, Cynthia Joanne (Book collections on Project MUSE., 2014)
The ledgers of merit and demerit were a type of morality book that achieved sudden and widespread popularity in China during the sixteenth and seventeenth centuries. Consisting of lists of good and bad deeds, each assigned a certain number of merit or demerit points, the ledgers offered the hope of divine reward to users ""good"" enough to accumulate a substantial sum of merits. By examining the uses of the ledgers during the late Ming and early Qing periods, Cynthia Brokaw throws new light on the intellectual and social history of the late imperial era. The ledgers originally functioned as.